Conflict management among principals at Islamic private secondary schools in Yala Province, Thailand - Apitree Adulpakdee (Institute of Education, International Islamic University Malaysia, 2010)
The purpose of this study is to evaluate the perceptions of principals and teachers toward conflict management at Islamic private secondary schools in Yala province, Thailand. Conflict is an inevitable situation in any organization including schools and this has challenges principals' abilities to resolve conflict. Principals who can manage conflicts in school effectively and efficiently will be able to foster a favorable teaching-learning environment which is conducive to learning. In this study, mix methods: survey and interview have been employed in order to obtain its objectives. The survey was distributed to 11 principals and 302 teachers through convenient sampling method and 6 out of 11 principals were interviewed using semi-structured interview. The findings revealed that all 11 schools confronted with some conflicts but the level of conflicts were not severe or uncontrolled and principals solved each conflict using various methods depending on the conflict situation. The types of conflict in schools were categorized into 4 types as follows: principal and teacher, teacher and teacher, teacher and student, and teacher and students' parents. There were three major causes of conflict in schools which were derived from different perceptions, ambiguously defined as responsibilities and different working styles. The methods and effective strategies that were used in managing and resolving conflict in schools depended heavily on the situation. However, two theories have been applied which were: 1) five conflict-handling modes by Thomas-Kilmann and 2) conflict cycles concept by Robinson-Difonso. As a result, several recommendations have been suggested for principals to improve the relationships between non-Muslim and Muslim teachers without bias and religious barriers, provide various complaining alternatives and state clearly teachers' responsibilities for each work. A future study has been recommended to evaluate the perception of teachers by interviewing them for eliciting information, pointing out a comparison between Islamic private secondary schools and public schools in the same provinces and comparing conflict management in schools between Muslim majority provinces such as Pattani, Yala and Narathiwat and Muslim minority province such as Bangkok.